2021
DOI: 10.3390/ijms222313035
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Stressors Induce Innate Immune Memory in Microglia and Contribute to Disease Risk

Abstract: Many types of stressors have an impact on brain development, function, and disease susceptibility including immune stressors, psychosocial stressors, and exposure to drugs of abuse. We propose that these diverse developmental stressors may utilize a common mechanism that underlies impaired cognitive function and neurodevelopmental disorders such as schizophrenia, autism, and mood disorders that can develop in later life as a result of developmental stressors. While these stressors are directed at critical deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 185 publications
0
11
0
Order By: Relevance
“…The neuroimmune system is the second established component of allostatic load that works in concert with HPA neuroendocrine signaling to modulate the stress response. Neuroimmune dysregulation is well-documented in clinical studies of neuropathology and is observed in response to ELS (74,204,205), and neurodevelopmental (206) and psychological (207-209) disorders. In fact, Bottaccioli et al (210) proposed that the "neuroendocrine-immune" network is a central molecular mediator between psychosocial stress and the psyche.…”
Section: The Neuroimmune System: a Link Between Mal And The Hpa Stres...mentioning
confidence: 99%
“…The neuroimmune system is the second established component of allostatic load that works in concert with HPA neuroendocrine signaling to modulate the stress response. Neuroimmune dysregulation is well-documented in clinical studies of neuropathology and is observed in response to ELS (74,204,205), and neurodevelopmental (206) and psychological (207-209) disorders. In fact, Bottaccioli et al (210) proposed that the "neuroendocrine-immune" network is a central molecular mediator between psychosocial stress and the psyche.…”
Section: The Neuroimmune System: a Link Between Mal And The Hpa Stres...mentioning
confidence: 99%
“…When looking at the neonatal brain, we found that gestational stress decreases the density of microglia on postnatal day 2. We know that microglia have receptors that respond to stress hormones in early development 86,87 and on embryonic day 14 prenatal restraint stress results in increased microglia density in the embryonic neocortical primordium of mice 88 while during the early postnatal period prenatal stress reduces the number of immature microglia in the corpus callosum and internal capsule, and promotes an accelerated microglial differentiation in brain regions such as the entorhinal cortex, parietal lobe neocortex, thalamus and septum in the neonatal rat 89 . In addition, the impact of stress on microbiota could also impact microglia via the release of various metabolites such as short‐chain fatty acids (SCFAs) or aryl hydrocarbon receptor (AhR) ligands 90 .…”
Section: Discussionmentioning
confidence: 99%
“…The neuroimmune system is the second established component of allostatic load that works in concert with HPA neuroendocrine signaling to modulate the stress response. Neuroimmune dysregulation is well-documented in clinical studies of neuropathology and is observed in response to ELS (68,186,187), and neurodevelopmental (188) and psychological (189)(190)(191) disorders. In fact, Bottaccioli et al (2022) proposed that the "neuroendocrine-immune" network is a central molecular mediator between psychosocial stress and the psyche (192).…”
Section: The Neuroimmune System: a Link Between Mal And The Hpa Stres...mentioning
confidence: 99%